CONQUER THE DIGITAL MARKET: MENAKLUKKAN PASAR DIGITAL - Zurrahmi; Puan Salsabillah, Della; Puspita, Dinda; Perkasa Tarigan, Andi; Zinedine, Zahara (UPMI Proceeding Series, 2023)
In the rapidly developing digital era, marketing is the main key to achieving business success. At the same time, intense competition in the digital market is driving marketers to adopt innovative marketing strategies to win over consumers and increase their market share. This research aims to explain the importance of innovative marketing strategies in conquering digital markets and provide practical guidance for your business success. In this research, we identify three main factors influencing marketing strategy innovation: digital technology, consumer behavior, and market competition. Digital technologies are playing a crucial role in shaping the way we interact with consumers, through social media, e-commerce platforms and sophisticated data analysis tools. Constantly changing consumer behavior must also be the main focus of marketers, with a deep understanding of consumer preferences, needs and expectations. In addition, the challenges faced in facing intense market competition need to be overcome by creating competitive advantages through product innovation, strategic differentiation and extraordinary customer experience. Through this research, we identified several innovative marketing strategies that can be implemented to increase the success of your business in the digital market. First, the use of creative and relevant content will help build emotional connections with consumers, strengthen brand awareness, and trigger higher interactions. Second, the use of personalization and segmentation techniques will allow marketers to deliver more targeted messages and increase consumer engagement. Third, collaborating with influencers and leveraging their endorsement power can help expand your brand reach and build consumer trust.